Investigation of the effect of anti-PIA/PNAG antibodies on biofilm formation in Escherichia coli - Shirmohammadpour, Mina; Mehrasbi, Mohammad Reza; Noshiranzadeh, Nader; Afshar, Davoud; Mansori, Kamyar; Mirzaei, Bahman (Frontiers in Microbiology, 2025)
Polysaccharide Intercellular Adhesin (PIA), a surface polysaccharide produced by Staphylococcus aureus and Staphylococcus epidermidis, is a compelling target for opsonic and protective antibodies against these bacteria. Escherichia coli has recently made an exopolysaccharide called poly-β(1,6)-N-acetylglucosamine (PNAG), biochemically indistinguishable from PIA. This study investigated the effect of antibodies generated against PNAG on biofilm formation and the opsonization activity of secreted antibodies in Escherichia coli. Following purification and structural confirmation of PIA polysaccharide from producing Staphylococcus epidermidis, the ability to inhibit biofilm and the function of secreted antibodies for the mentioned polysaccharide were evaluated using semi-quantitative methods in a mouse model. Subsequently, the opsonic activity of antibodies targeting Escherichia coli strain ATCC 25922 was evaluated. The extracted polysaccharide was confirmed using FTIR, NMR, and colorimetric methods, and the results showed that the purified PIA induced protective antibodies with 40.48% opsonization properties in E. coli. The sera of the PIA-immunized groups showed a significant increase in antibody production and protective IgG titer levels compared to the control group. Also, the antibodies produced showed a substantial difference in inhibiting biofilm production in vitro compared to non-immunized serum. Antibodies directed against PIA with a lethality of 40.48% showed a significant effect on the absence of biofilm formation in E. coli. Despite the opsonic properties of the antibodies for E. coli, the simultaneous impact of these antibodies on infections caused by S. epidermidis and E. coli may have a role that requires further investigation and studies in animal models.